Applicability study of a deflector in ventilation and air conditioning duct tees based on an analysis of energy dissipation. Issue 184 (January 2019) - Gao, Ran; Li, Haimeng; Li, Angui; Liu, Kaikai; Yu, Shengrui; Deng, Baoshun
Abstract: Energy consumption due to the hydraulic resistance of a duct system accounts for approximately 30–50% of the total energy consumption in air conditioning systems. It is widely believed that the installation of a deflector on duct fittings under any operating conditions can reduce resistance and thus reduce energy consumption. This paper discusses the applicability of a deflector in ventilation and air conditioning duct tees through full-scale experiments and numerical simulations. The energy dissipation field was used to characterize the resistance field. The optimal deflector position under different flow ratios and tee forms was studied, and the influence of the deflectors on the energy dissipation field was analyzed. This study shows that five types of typical deflector placements in the tee can reduce the resistance when the velocity ratio between the branch duct and the main duct is less than 0.4, with a resistance reduction ranging from 5.2% to 38.4%. The optimal deflector position is not related to the type of tee. The deflector placement can effectively reduce the energy dissipation on the lower edge of the deflector. The calculated results are verified by a full-scale experiment and by previous studies, ensuring the accuracy of the present study. Highlights: The applicability of deflector in ventilation duct is analyzed. The energy dissipation field is used to characterize the resistance field. The optimal deflector position under different flow ratios and tee forms is studied.